APPLICATION OF FINE COMPOSITION DESIGN WITH ETHNIC ELEMENTS - Budiman (CENTRAL ASIA AND THE CAUCASUS, 2022)
Processing visual elements into compositions in a flat plane is a task that is always carried out by elementary-level students in study programs related to fine arts, especially in the Graphic Design study program at Widyatama University. In even semesters, the follow-up course is compositional design that is applicable. The design elements to be explored are ethnic ornaments, such as; ethnic Javanese, ethnic Sumatran, ethnic Papuan, and also ethnic from other continents such as from ancient Egypt and oriental. The design process begins with data analysis of design elements that will be explored by inserting it into a geometric grid as the first alternative and by stacking objects as the second alternative. The next design process is that each student's work consults the lecturer with special treatment methods or individual treatment. The development of the design composition is carried out on a case-by-case basis based on the analysis of ethnic forms, ethnic colors, and nirmana compositions that prioritize dynamism, balance, and unity. The result of the creative process makes the flat nirmana composition a new visualization, but the characteristics of the ethnic origin still remain as its trademark as the initial identity.